Kelayakan Air Tanah untuk Irigasi Pertanian Menggunakan Sodium Arbsoption Ratio (SAR) - Anidya Aprila Permatasari; Septian Vienastra (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Irrigation has an important role and is one of the keys to success in increasing rice production in paddy fields. Trimulyo Village is one of the areas in Jetis District, Bantul Regency has the majority of people as farmers. There is no information about groundwater quality as agricultural feasibility in the area is the background of this research. The purpose of this study was to determine the feasibility of groundwater quality for agricultural irrigation using the Sodium Adsorption Ratio (SAR) method in Trimulyo Village, Jetis District, Bantul Regency, Special Region of Yogyakarta. The method used in this study was the testing of 2 groundwater samples in the laboratory and field observation of geology and geomorphology conditions. The parameters used are chemical parameters which include Sodium or Sodium (Na), Calcium (Ca), and Magnesium (Mg). Based on the results of laboratory tests and data analysis, that groundwater sample 1 had a SAR value of 0,63 then groundwater sample 2 had 0,75. Both groundwater samples have a water classification of Excellent or Very Good for agricultural irrigation.